Application of Oketani Massage as a Complementary Therapy to Support Exclusive Breastfeeding Among Postpartum Mothers at a Community Health Post in Bogor, Indonesia - Triswanti; Susanti Tungka; Halma Neyla Abdullah Alfat; Lista Dwi Ikawati; Nabih; Refa Destiani (CV. Get Press Indonesia, 2026)
Exclusive breastfeeding is a key public health strategy to improve maternal and infant health outcomes. However, postpartum mothers often experience lactation problems such as inadequate milk production, breast engorgement, and discomfort, which may hinder successful breastfeeding practices. This community service program aimed to apply Oketani massage as a complementary therapy to support exclusive breastfeeding among postpartum mothers at a community health post (Posyandu) in Bogor, Indonesia. The program was conducted as asigle-group a community-based promotive and preventive approach involving health education, demonstration, and guided practice of Oketani massage techniques. Participants consisted of five postpartum mothers . Evaluation was conducted using oral pre-test and post-test assessments and direct observation of participants’ skills.. The results showed that prior to the intervention, all participants (5 mothers, 100%) had no knowledge of Oketani massage. After the demonstration and guided practice, all participants were able to explain the definition, benefits, objectives, and procedures of Oketani massage. Participants also reported greater confidence in applying the massage technique to support breastfeeding. These findings suggest that Oketani massage education through demonstration is a simple and feasible complementary intervention that can be integrated into community-based maternal health services to support exclusive breastfeeding practices.